ANALISIS KEBIJAKAN KESEJAHTERAAN GURU TERHADAP PENINGKATAN KUALITAS PENDIDIKAN - Nabila Rahma Aulia; Embun Luthfi Shodiqoh; Sania Putri Cahyaningrum (Universitas Islam Malang, 2023)
Providing teacher welfare and compensation is an effort to retain teachers with good talents and abilities when teaching and learning. Well-being is very useful and meaningful for a teacher’s physical and mental needs. Through a teacher welfare program that is regulated based on government regulations that are fair and obedient to government regulations, it is an effort to improve the welfare of a teacher so that he remains enthusiastic at work, and can also provide high and good quality education. The form of teacher welfare is in the form of salary, such as basic salary and additional salary that comes from government allowances. This study aims to determine the effect of teacher welfare on the quality of education in Indonesia. This study method is a literature study and uses a qualitative approach so that the data obtained is more in-depth with the help of various facts in the field.